Embryonic esophageal rhabdomyosarcoma in an adult male: A case report and literature review - Zhang, Xiaoman; Li, Guang (Frontiers in Oncology, 2022)
Abstract : Rationale: Esophageal rhabdomyosarcoma is a rare invasive tumor derived from striated muscle cells or mesenchymal cells that differentiate into striated muscle(1). This tumor has a high degree of malignancy and extensive metastasis. Most of the patients are at an advanced stage when presenting to the hospital, and the prognosis is very poor(2). Patient concerns: A 54-year-old male presented with dysphagia as the initial symptom. Gastroscopy showed an irregular protuberant lesion about 18–22 cm from the incisor. The lesion was observed to be pathological under gastroscopy and was diagnosed as an (esophageal) sarcoma. Diagnosis: Embryonic esophageal rhabdomyosarcoma. Interventions: After receiving two cycles of DP (docetaxel and cisplatin) chemotherapy in the local hospital, the patient received 60 Gy of radiotherapy in 30 fractions combined with chemotherapy at our hospital. Dysphagia was relieved, and the tumor appeared significantly shrunken on imaging after the treatment. Outcomes: Lung metastasis occurred 1 month after radiotherapy, and the patient died of pulmonary edema on March 11, 2022. Lessons: Previously reported cases of embryonic esophageal rhabdomyosarcoma are few(1, 3, 4). Theoretically, the disease should occur in adolescents; however, our case was in a middle-aged man and the tumor was in an uncommon location: the upper segment of the esophagus. Moreover, the patient initially had good response to the combination of radiotherapy and chemotherapy. Although he died 8 months after diagnosis, the presented data represent a valuable resource for understanding the survival benefits of treating embryonic esophageal rhabdomyosarcoma patients with radiotherapy combined with chemotherapy. In addition, we reviewed the previously reported literature, and a total of 17 cases of esophageal rhabdomyosarcoma were identified and analyzed. Abbreviations: MRI = magnetic